Silurian freshwater arthropod from northwest China. (29th March 2023) - Zong, Ruiwen; Edgecombe, Gregory D.; Liu, Bingcai; Wang, Yi; Yin, Jiayi; Ma, Juan; Xu, Honghe
Abstract: Animals breaking away from the sea was a revolutionary event in the evolution of life. Arthropods were the earliest metazoans to move onto land, and although a few Silurian freshwater and/or terrestrial arthropods have been found so far, these records are all from Laurussia. Here, we describe a new freshwater arthropod, Maldybulakia saierensis sp. nov., from the western Junggar, northwest China. Evidence from co‐occurring spores and body fossils of plants is presented in support of a Silurian (Pridoli) age for this new Maldybulakia species, alongside palaeosalinity data in support of our interpretation of it having lived in a freshwater environment. The discovery of this species brings forward the earliest appearance of the Maldybulakia, previously known from the Devonian of Kazakhstan and eastern Australia, to the late Silurian. It is the oldest body fossil record of a putatively freshwater arthropod outside Laurussia, and greatly expands their palaeogeographical distribution. In the middle and late Silurian, the discovery of freshwater arthropods on multiple plates/terranes, as well as their morphological diversity during this period, suggests that arthropods had left the marine environment by the early Silurian or even earlier.